Globalisasi dan identitas budaya Indonesia melalui aplikasi tiktok - Oktarina Oktarina; Sarmiati Sarmiati; Asrinaldi Asrinaldi (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This study aims to explain globalization and cultural identity in Indonesia through the Tiktok application. In Indonesia, the Tiktok application is one of the most popular applications by various groups. Through globalization, communication technology has a significant influence on the identity and behavior of the Indonesian people. This research was conducted using a qualitative descriptive method which is an assessment method to reveal a situation, fact, and phenomenon. The results of the study explain that the Tiktok application is a social media that has begun to erode local identity and Indonesian culture